The Impact of Digital Storytelling Applications on Enhancing Critical Thinking Abilities in Higher Education Students - Rosyid, Abdur; Nur Fauzia; Darma, Diana Budi; Abida, Fithriyah Inda Nur; Iye, Risman (Room of Civil Society Development, 2025)
This study aims to examine the impact of using digital storytelling applications on the development of students' critical thinking skills within a learning context. It employs a qualitative approach, using observation, interviews, and document analysis to gather data. 46 students are participated in a digital storytelling project for 1 semester that required them to organize, analyze, and critically present information using digital applications such as Adobe Spark and Canva. The findings indicate that the use of digital storytelling applications significantly contributes to the development of students' critical thinking skills. These applications enable students to integrate various media—such as text, images, audio, and video—encouraging them to think critically about the most effective way to convey messages. Additionally, digital storytelling applications prompt students to evaluate information more thoroughly, develop strong arguments, and present them creatively and logically. Based on the research data, digital storytelling applications are also shown to be effective in enhancing students' critical thinking skills and hold potential for broader integration into education as innovative and interactive learning tools.